Assessing Sharia-Based Service Quality for Sustainable Banking Management in Islamic Financial Institutions - Aprianti, Vina; Mu'arrif, Zul Ihsan (Institut Agama Islam Negeri Parepare, 2025)
Purpose – This study evaluates customer perceptions and experiences of Sharia-based service quality in Islamic financial institutions, emphasizing its role in fostering sustainable banking management. It explores how the alignment between service delivery and Islamic principles influences customer satisfaction, loyalty, and long-term institutional resilience. Method – A qualitative descriptive approach was adopted, utilizing in-depth interviews with selected customers who actively engage in banking transactions. Purposive sampling ensured the inclusion of participants capable of providing nuanced insights into service delivery and its Sharia compliance. Findings – Results reveal that adherence to Sharia principles, combined with professionalism, transparency, and customer-centered interactions, strengthens customer trust and satisfaction. Positive experiences often translate into loyalty and advocacy, while customer knowledge, cultural values, and needs further shape perceptions. The integration of Islamic ethical values into service quality emerges as a strategic driver for sustaining competitive advantage. Practical implications – Islamic banks should integrate Sharia compliance with a sustainability-oriented service culture through continuous staff training, customer education, and quality assurance mechanisms. This dual focus enhances not only regulatory adherence but also the long-term viability of Islamic financial institutions. Originality/value – This research extends the literature on Islamic service quality by linking Sharia compliance to sustainable banking management, offering actionable insights for policymakers, managers, and practitioners seeking to optimize both customer experience and institutional sustainability